(untitled) (Biocenosis, 2025)
The metropolitan area of Veracruz–Boca del Río and Alvarado, in the state of Veracruz, Mexico, has undergone environmental changes due to human activities. This study analyzed the subjective perception of young volunteers regarding beach cleanup activities on the Veracruz Riviera. A mixed-methods approach was employed, using structured and open interviews to characterize the participants - comprising 40 volunteers and three environmental leaders - and to explore their perceptions of beach cleaning and its impact on local communities. Qualitative and quantitative data were analyzed using the QDA Miner LT software. The results showed that the age group with the highest representation was 31 to 40 years, and that women were the most active participants in the cleanup campaigns. The most common solid waste was plastic. The study concludes that beach cleanup strategies foster a greater commitment to environmental issues, although they are still in the early stages. Future research lines are proposed to examine the role of Veracruz women in environmental action and education.